Integration of Sustainability Aspect and Company Strategy in Indonesia Technology Sector - Firman El Amny Azra (Enrichment : Journal of Management, 2022)
The sustainability dimensions of business activity have attracted increasing attention from business stakeholders and changes in societal context of business in the future are constraining company ability to pursue unsustainable value creation. Considering the instrumental role of external environment in effective strategy formulation, this paper aims to contribute in theory development and evaluate the practical implementation by analyzing integration of sustainability aspect with company strategy. This research carried out on a sample of 10 publicly listed tech company in IDX. This study uses descriptive qualitative research method using secondary data The results of this study suggest partial integration of sustainability aspect with company strategy with a number of required improvements in critical areas of strategy formulation in order to capture the full potential of sustainability integration with company strategy